ChemInform Abstract: Emergence of Pyrido Quinoxalines as New Family of Antimalarial Agents. Issue 38 (10th September 2014) - Chandra Shekhar, A.; Shanthan Rao, P.; Narsaiah, B.; Allanki, Aparna Devi; Sijwali, Puran Singh
Abstract A series of pyridoquinoxaline derivatives (24 examples) are synthesized and evaluated for their antimalarial activities against chloroquine sensitive (3D7) and drug resistant (Dd2) strains of Plasmodium falciparum.